The Oversight Role of the Ombudsman of the Republic of Indonesia: A Comparative Study of the National Ombudsman and the Parliamentary Ombudsman (Riksdagens Ombudsman): Peran Pengawasan Ombudsman Republik Indonesia: Studi Komparatif Nationale Ombudsman dan Riksdagens Ombudsman - Al'Anam, Muklis; Prabowo, Hendro (Lex Renaissance, 2025)
The development of legal science is very rapid, so it is inseparable from the concept of the division of powers of state institutions. The authority is used to carry out public services and the function of the citizens' human rights approach. This approach is a form of legal protection for the people as the main part of administrative law. One of the holders of legal protection powers for citizens is the Ombudsman. The Ombudsman is a projustitia state institution in various countries and ensures the legal protection of citizens against government actions. However, in this context in Indonesia, the position of the Ombudsman as a concept of legal protection through an administrative law approach has not been maximised with a number of authorities. This problem occurs because administrative law in Indonesia does not have a special position in its legal order, one example is that there is no codification of Indonesian administrative law like in other countries such as the Netherlands having Algemen Wet Bestuurrecht (AWB). In Indonesia, it forms a special rule or material guideline, namely Law Number 30 of 2014 concerning Government Administration which cannot be said to be a material administrative law concept. This is because the regulation is not theoretically based on administrative law. So, it is necessary to have an administrative law policy in terms of preventive and repressive law enforcement. Therefore, this research uses the norm method based on statutory, conceptual and comparative legal approaches. With legal materials using comparative juridical analysis of the ombudsman institutional system in the Netherlands and Sweden. So that this research shows a much different concept of authority between the Indonesian Ombudsman, the Dutch Nationale Ombudsman functions as a government watchdog mentioned in Article 78a of the Dutch Constitution, and the Riksdagens Ombudsman. Sweden which is an organ of parliament to carry out supervision of the executive as a state organiser by issuing legal products, namely recommendations and also has the authority to conduct conciliation and mediation.